2018
DOI: 10.3390/atmos9010020
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Observations at Gaisberg Tower

Abstract: Abstract:We report the occurrence of X-rays at ground level due to cloud-to-ground flashes of upward-initiated lightning from Gaisberg Tower, in Austria, which is located at an altitude of 1300 m. This is the first observation of X-ray emissions from upward lightning from a tower top located at high altitude. Measurements were carried out using scintillation detectors installed close to the tower top in two phases from 2011 to 2015. X-rays were recorded in three subsequent strokes of three flashes out of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…(2012) with emphasis on subsequent strokes, they observed that not all leaders of the same flash produced detectable X‐rays. Due to the lower air density and consequently lower X‐ray absorption, observations of high‐energy radiation from thunderstorms were conduced at high‐altitude towers (e.g., Hettiarachchi et al., 2018; Montanyà et al., 2014) and on aircraft (e.g., Kochkin et al., 2017; Skeie et al., 2020; Smith et al., 2011). Recently, Saba et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012) with emphasis on subsequent strokes, they observed that not all leaders of the same flash produced detectable X‐rays. Due to the lower air density and consequently lower X‐ray absorption, observations of high‐energy radiation from thunderstorms were conduced at high‐altitude towers (e.g., Hettiarachchi et al., 2018; Montanyà et al., 2014) and on aircraft (e.g., Kochkin et al., 2017; Skeie et al., 2020; Smith et al., 2011). Recently, Saba et al.…”
Section: Introductionmentioning
confidence: 99%
“…A statistical study of X-ray emissions was published by Mallick et al (2012) with emphasis on subsequent strokes, they observed that not all leaders of the same flash produced detectable X-rays. Due to the lower air density and consequently lower X-ray absorption, observations of high-energy radiation from thunderstorms were conduced at high-altitude towers (e.g., Hettiarachchi et al, 2018;Montanyà et al, 2014) and on aircraft (e.g., Kochkin et al, 2017;Skeie et al, 2020;Smith et al, 2011). Recently, Saba et al (2019) measured X-ray emissions in coincidence with a dart leader using high-speed video and pointing out the role of the leader orientation in the X-ray detection.…”
mentioning
confidence: 99%
“…Lightning emits X-rays. Although progress has been achieved in quantifying some properties of the lightning-leader X-ray emission in natural, rocket-triggered, and upward lightning (e.g., Moore et al, 2001, Dwyer et al, 2003, Dwyer et al, 2004, Dwyer et al, 2005, Dwyer et al, 2011Saleh et al, 2009;Yoshida et al, 2008;Howard et al, 2008, Howard et al, 2010Mallick et al, 2012;Hettiarachchi et al, 2018), it is still uncertain why not all strokes in the same flash and not all leader steps in the same stroke produce detectable X-rays. Howard et al (2010) reported observations of leader electric fields and generation of energetic radiation close to triggered lightning.…”
Section: Introductionmentioning
confidence: 99%
“…Lightning detection technology has always played an important role in lightning research [1][2][3]. With the development of microelectronics and optoelectronic technology, lightning detection methods have been improved significantly since the 1970s [4][5][6][7][8][9][10][11][12][13][14][15]. Therefore, people have made breakthrough progress in understanding the distribution structure of positive and negative charge layers in thunderstorms and the discharge processes of intra-cloud flash (IC) and cloud-to-ground flash (CG) at various stages, making it possible to conduct fine research on the lightning development process [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%